2019
DOI: 10.3390/beverages5010008
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Field Extraction and Antioxidant Activity Determination of Moringa oleifera Dry Leaves: A Comparative Study with Other Extraction Techniques

Abstract: The scope of this work was to determine the possibility of the application of the pulsed electric field (PEF) technique to the production of extracts from Moringa oleifera plant material (freeze-dried leaves). Various PEF conditions (pulse duration—PD; and pulse interval—PI) were tested. A field strength of 7 kV/cm was used. The total phenols in the extracts were evaluated by the Folin–Ciocalteu method and the antioxidant activity was evaluated by the radical scavenging activity (DPPH•), ferric reducing antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 46 publications
1
60
0
Order By: Relevance
“…Pretreatment with PEF has been reported to significantly increase the efficiency of betalain extraction from beetroot (P < 0.05) [11]. Additionally, a low pulse duration with a high pulse interval of PEF has been reported to increase the extraction efficiency of dry Moringa oleifera leaves [15]. PEF-assisted maceration of red grape juice also promoted wine color quality and the polyphenolic profile [16].…”
Section: Introductionmentioning
confidence: 97%
“…Pretreatment with PEF has been reported to significantly increase the efficiency of betalain extraction from beetroot (P < 0.05) [11]. Additionally, a low pulse duration with a high pulse interval of PEF has been reported to increase the extraction efficiency of dry Moringa oleifera leaves [15]. PEF-assisted maceration of red grape juice also promoted wine color quality and the polyphenolic profile [16].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, PEF treatment increased the extraction yield of polyphenols in tea leaves by two times compared to the conventional thermal methods without any significant changes in phenolic composition as evidenced by mass spectrometry analysis (Liu et al, 2019). Bozinou et al (2019) reported that the highest extraction yield in PEF treatment was found at a field strength of 7 kV/cm for 40 min in the extraction of phenolics from freeze-dried leaves of Moringa oleifera.…”
Section: Pulsed-electric Field Extraction (Pef)mentioning
confidence: 99%
“…The PEF equipment used was provided by Val-Electronic (Athens, Greece), and included the static bench scale system, reported previously (Bozinou et al, 2019), accompanied by another high voltage power generator (from Eisco, India). The model of the batch processing chamber (TC) was adapted from a design of cylinder type electrodes (Ohshima and Sato, 2004) and consists of a coaxial stainless steel electrode [5 mm in diameter and 165 mm high, Figure 1(1)] placed inside a bronze cylinder [1 mm thick, 155 mm high and 30 mm outer diameter Figure 1(2)] with a closed flat bottom.…”
Section: Pef Equipmentmentioning
confidence: 99%
“…Conventional extraction methods require extended extraction times, high purity solvents, often offer low extraction selectivity and, finally, in some cases are responsible for the thermal decomposition of sensitive compounds (Bozinou et al, 2019). For the above reasons, new extraction techniques have been introduced.…”
Section: Introductionmentioning
confidence: 99%